Encapsulation of saffron and sea buckthorn bioactives: Its utilization for development of low glycemic baked product for growing diabetic population of the world. (May 2021) - Gani, Asir; Jan, Romee; Ashwar, Bilal Ahmad; Ashraf, Zanoor ul; Shah, Asima; Gani, Adil
Abstract: In this study, bioactive compounds from saffron ( Crocus sativus L.) and sea buckthorn ( Hippophae rhamnoides L.) were extracted using ultrasound-assisted extraction method. The extracted bioactive compounds were encapsulated in sodium alginate. The encapsulation efficiency of SE (encapsulated saffron) and SBE(encapsulated sea buckthorn) was found to be 60.303%, and 64.662%, respectively. Further, the encapsulated powder were added in the wheat flour (1%) to prepare functional cookies and its effect on structural, thermal and antioxidant properties were studied. FTIR revealed a difference in the intensity of peaks between free and encapsulated saffron (SF and SE) and sea buckthorn (SBF and SBE) bioactives. DPPH scavenging activity, reducing power, total phenolic content and lipid peroxidation inhibition were performed which displayed that antioxidant activity was significantly higher. The in-vitro digestibility assay of cookies enriched with saffron and sea buckthorn showed slow digestion of cookies that means it hinders starch digestion and this approach is expected to design low glycemic bakery product for growing diabetic population of the world. Also, the cookies developed from encapsulated powder showed better consumer acceptability as compared to cookies with free bioactives. Highlights: Food grade biopolymer sodium alginate was used as encapsulating agent. Encapsulation efficiency and bioactive retention increased. Retention of nutraceutical potential was evaluated using different assays. Saffron and sea buck thorn polyphenols reduced the starch degradation. Baked products with low glycemic index for diabetic population was produced.